Individualism and Egalitarianism Can Kill: How Cultural Values Predict Coronavirus Deaths Across the Globe - Güss, C. Dominik; Tuason, Ma. Teresa (Frontiers in Psychology, 2021)
While in some countries, many people have died due to the coronavirus (COVID-19), in other countries, only a few have died. Based on the cultural values theory, our first hypothesis was that in countries that are predominantly individualistic, the number of deaths will be high, whereas in countries with predominantly collectivist values, the number of deaths will be low. Our second hypothesis was that countries with high power distance and hierarchy will have fewer deaths compared to countries with low power distance and egalitarianism. The hypotheses were tested by referring to two different value studies (Hofstede's study of 76 countries and Schwartz's study of 75 countries) while also controlling for GDP per capita, Gini index, population density, median age per country, and BMI per country. Of the five control variables GDP and BMI significantly predicted coronavirus deaths. Taking into account GDP, Gini index, population density, median age, and BMI, hierarchical regression analyses confirmed the first hypothesis on individualism and the second hypothesis on egalitarianism. Therefore, in the case of this current pandemic, group-oriented and collectivist values and low egalitarianism values lead to specific health-related behaviors that ultimately keep more people alive.